Perbedaan Gaya Kepemimpinan di Sekolah yang Bagus dan Kurang Bagus - Siregar, Delisma; Saragih, Emi Juwita; Sari, Kartika; Winara, Winara; Lubis, Wildansyah (Pusdikra Publishing, 2024)
This article discusses a comparison of leadership in the context of good and less good schools. The principal's leadership style basically means a manifestation of the behavior of a school principal, which concerns his ability to lead the school. Elementary Schools (SD) are of course part of basic educational institutions to instill values, attitudes and aesthetics so that quality leaders are needed with the right leadership style. Leadership style influences a person's success in the school he leads, especially in influencing the behavior of his subordinates and success is much influenced by leadership style. School principals should provide work instructions to teachers so that carrying out their work becomes easier. Leadership in educational institutions is very important to achieve goals. academics and student character development. However, leadership in good schools, elementary school A and less good elementary school B, has differences in leadership style. This study uses a qualitative approach with data collection techniques through in-depth interviews with the leaders of good schools at Sdn A and less good Sdn B. Data analysis was carried out using the thematic analysis method. The results of the research show that leadership in good schools, Sdn A, is more focused on achieving academic targets, while leadership in less good schools, Sdn B, on the other hand, is not focused on achieving academic targets or anything else. In the context of educational development in Indonesia, this research can provide insight and understanding of the differences in leadership in two different types of educational institutions. It is hoped that the results of this research can provide guidance for school leaders in improving the quality of leadership and educational development in Indonesia. Every leader has a leadership style that is different from one leader to another. Furthermore, try to avoid reprimanding in public if a teacher makes a mistake in their work and continue to guide teachers so that they are more comfortable at work. Apart from that, we should improve and maintain patterns that have been good so far and increase the values ??of a positive leadership style in order to increase achievement motivation and at the same time improve teacher performance.